Optimizing stability in AO/OTA 31-A2 intertrochanteric fracture fixation in older patients with osteoporosis. Issue 5 (May 2018) - Zhang, Chi; Xu, Bo; Liang, Guanzhao; Zeng, Xianshang; Zeng, Dan; Chen, Deng; Ge, Zhe; Yu, Weiguang; Zhang, Xinchao
Objectives: To compare the functional and radiographic outcomes of InterTAN nail (IT) and proximal femoral nail anti-rotation (PFNA) for managing primary AO/OTA 31-A2 intertrochanteric hip fractures (IHFs) in older osteoporotic patients. Methods: Patients aged 60 years or older who received surgical treatment for IHFs (AO/OTA 3.1A2.1-A2.3) with IT or PFNA were retrospectively evaluated. The primary outcome was the postoperative treatment failure rate. The secondary outcome was the Harris Hip Score (HHS). Results: A total of 326 osteoporotic cases (326 hips: IT, n = 162; PFNA, n = 164) were assessed with a mean follow-up of 43.5 months (range, 38–48 months). For the entire cohort, the incidence of postoperative treatment failure (periprosthetic fracture and reoperation) was 29/326 (8.9%); the IT-treated cohort (7/162, 4.3%) had a significantly lower rate compared with the PFNA-treated cohort (22/165, 13.3%). The incidence of postoperative periprosthetic fractures was significantly lower in the IT-treated cohort than in the PFNA-treated cohort (2.5% vs 7.9%). The postoperative HHS at the final follow-up was not significantly different between the groups. Conclusion: IT might show a better outcome in managing osteoporotic AO/OTA 31-A2 IHFs in terms of periprosthetic fracture and reoperation compared with PFNA.